Analysis of the Relationship between Self Efficacy and Other Factors against Adherence to Taking Medication in Patients with Diabetes Mellitus at the Secretariat of the Supreme Court of the Republic of Indonesia - Nita Sari Septiaji; Omega DR Tahun (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
According to Indonesian data, in 2022 there will be 19.5 million Indonesians aged 20-79 who have diabetes. Indonesia is the country with the fifth largest number of diabetics in the world. Patients with diabetes mellitus require treatment, management and control of treatment in the long term. Control of treatment in people with Diabetes Mellitus often experiences several obstacles, because people with diabetes mellitus will experience many changes in their lives starting from managing their diet, exercise, controlling blood sugar, taking medication regularly and other activities that need to be carried out for the rest of their lives. This type of research is analytic quantitative with a cross-sectional study design. The sample selection technique was carried out by means of non-probability sampling, and the type of statistical test used was kai square. The population in this study were all employees suffering from diabetes mellitus who visited the RI Supreme Court Secretariat Clinic, the sample size was 37 respondents. Based on the results of statistical tests showed that the factors associated with medication adherence in diabetics, namely: self-efficacy (p value = 0.036), family support (p value = 0.018), and motivation (p value = 0.016). For people with diabetes mellitus to be more obedient in taking medication in order to control blood sugar levels, because the impact of high blood sugar levels is not only diabetes mellitus, but can be fatal to kidney damage, eyes, heart attacks, strokes and other diseases.